Immuno-therapeutic evaluation of Withania somnifera in bovine mastitis - SHAFI, TAWHEED AHMAD; BANSAL, BALJINDER KUMAR; GUPTA, DHIRAJ KUMAR (The Indian Journal of Animal Sciences, 2020)
Mastitis is a severe problem of diary animals, and concept of non-antibiotic strategies for its prevention is gaining attention. An in vitro antibacterial evaluation of Withania somnifera against bovine mastitis pathogens, followed by its in vivo therapeutic trial was carried out in 20 HF × Sahiwal dairy cows with at least one specific subclinical mastitis quarter. W. somnifera root extract used in this study showed in vitro antibacterial activity of 78.19% and 55.67% against Staphylococcus aureus and Escherichia coli respectively. The treatment group was administered orally W. somnifera root powder @ 500 mg/kg body weight daily, divided into two doses for 7 days, and was evaluated for elimination of intramammary infections, subsiding of udder inflammation and immunomodulation. The therapy could eliminate 64.28% of intramammary infections (c2 = 4.14), and resulted in a significant reduction in somatic cell count and ceruloplasmin concentration, therefore, subsiding udder inflammation and improving milk quality. Immunomodulation potential of the herb was evident from significant increase in phagocytic activity/phagocytic index along with enhanced lactoperoxidase and myeloperoxidase activities in the milk of treated cows.